2014
DOI: 10.1111/cei.12302
|View full text |Cite
|
Sign up to set email alerts
|

Serum autoantibodies directed against transglutaminase-2 have a low avidity compared with alloantibodies against gliadin in coeliac disease

Abstract: SummaryCoeliac disease is characterized by intolerance to gliadin and related gluten components present in wheat, barley and rye. Coeliac disease patients harbour antibodies directed against alloantigens such as gliadin, but also against the autoantigen transglutaminase-2 (TG2). The type and quality of antibody responses provides insight into the underlying immune activation processes. Therefore, in this study we have analysed the avidity of the antibody response directed against the autoantigen TG2 and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…For example, avidities of anti-amyloid-b antibodies in Alzheimer's disease were characterized by lower avidities [34]. An interesting comparison between avidities of antibodies against recall antigens and autoantigens suggested that regulation of immune B cell response can differ [35][36][37]. While the avidities of autoantibodies against citrullinated and carbamylated proteins, or tranglutaminase-2 tend to be low, avidities against recall antigens, such as tetanus toxoid, diphtheria toxoid, or gliadin, can be high despite their low titre.…”
Section: Discussionmentioning
confidence: 99%
“…For example, avidities of anti-amyloid-b antibodies in Alzheimer's disease were characterized by lower avidities [34]. An interesting comparison between avidities of antibodies against recall antigens and autoantigens suggested that regulation of immune B cell response can differ [35][36][37]. While the avidities of autoantibodies against citrullinated and carbamylated proteins, or tranglutaminase-2 tend to be low, avidities against recall antigens, such as tetanus toxoid, diphtheria toxoid, or gliadin, can be high despite their low titre.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, most recently, a Spanish group, found that intestinal ϒδ+ intraepithelial lymphocyte cytometric pattern is more accurate than subepithelial deposits of anti -IgA-TG2 ABs for CD diagnosis [19]. Anti TG2 autoantibodies expose a lower avidity compared with alloantibodies directed against gliadin, indicating different regulation or site of initiation of these humeral response [20]. Finally, exploring the celiac antibody binding to TG2, a single conformational TG2 epitope contributed by three domains was described to be critical for the ABs binding and their effects [21].…”
Section: Anti Tg2 Abs Secretion Binding and Distributionmentioning
confidence: 99%
“…It is assumed that the high affinity (avidity) complexes of antigen B-cell receptor (i.e., surface antibodies associated with signaling molecules) could promote an extrafollicular B-cell response leading to an increasing number of plasma cells secreting antigen-specific antibodies [75]. Interestingly, an extrafollicular response or a short-time germinal response is assumed in the development of specific B-cells producing the low avidity autoantibodies against the key autoantigen of celiac disease, i.e., tissue transglutaminase [76,77]. Unfortunately, the histological analysis of the small intestinal mucosa is not usually performed in a follow-up of these patients.…”
Section: The Possible Similarity Between Oat and Wheat Amylase/trymentioning
confidence: 99%